Empowering Women and Men Vegetable Farmers with Lersha Digital Platform - HER+ initiative, Ethiopia - Nchanji, Eileen; Cosmas, Lutomia; Ketema, Dessalegn (CGIAR GENDER Impact Platform, 2024)
CGIAR's Gender Equality initiative (HER+) work package Empower is working with Green agro solutions to integrate social innovations through the Lersha digital platorm for increased empowerment, resilience, income and food security. Lersha offers a comprehensive digital service for smallholder farmers, providing fast and affordable farm inputs, mechanization services, and agro-climate advice. In rural communities, women and men tirelessly cultivate their lands but struggle with quality inputs and reliable markets. The Lersha Digital Platform changes this by connecting farmers to a vast network of trusted dealers and off-takers. It empowers farmers through Vegetable Business Networks, promoting collaboration, knowledge sharing, and sustainability. With Lersha, women farmers are connected, empowered, and thriving. Transform your farm with Lersha today—join the revolution and see the difference.